Internal load of female varsity ice hockey players during training and games during a season - Bigg, J. L.; Gamble, A. S. D.; Spriet, L. L. (International Journal of Sports Medicine, 2022)
This study quantified internal load, using sessional rating of perceived exertion (sRPE) and heart-rate derived training impulse (TRIMP), of female varsity ice hockey players throughout a season. Twenty-four female (19.8±1.4 yr, 68.0±6.9 kg) varsity ice hockey players participated in this prospective cohort study. Internal load was captured using sRPE and TRIMP for each on-ice session. Internal load was significantly higher (p<0.05) for games (sRPE: 324±202 AU, TRIMP: 95±60 AU) compared to training (sRPE: 248±120 AU, TRIMP: 68±32 AU). Overall, goalies had a higher internal load than forwards (sRPE and TRIMP) and defence (TRIMP), with no differences between forwards and defence. Micro-cycle periodization was present, with training sessions several days prior to game days having the highest internal load (sRPE and TRIMP) and tapering down as subsequent training sessions approached game day. For the meso-cycle assessment, for both training and competition combined, the post-season sRPE was greater than the pre-season (p=0.002) and regular season (p<0.001). Lastly, the association between sRPE and TRIMP, revealed a large, statistically significant relationship (r=0.592, p<0.001). Internal load was greater during competitions, training sessions and subsequent internal loads suggested prioritization around game days, the post-season phase demanded the highest internal load and there was a strong correlation between sRPE and TRIMP.